Morphological Character of Clove “Raja” (Syzygium aromaticum L.), Endemic to Maluku, Indonesia - Wattimena, Anna Yuliana; Mahulette, Asri Subkhan; Makaruku, Marlita Herlin; Lating, Muhammad Fajri Aditthia (Journal of Tropical Crop Science, 2023)
Clove “Raja” is one of the local Maluku clove germplasm, which has characteristics similar to cultivated cloves and wild types. Until now, very limited information that are available on the morphological character of clove “Raja”. This study aims to provide basic information on the morphological diversity of “Raja”. The study was conducted at the location of the distribution of cloves “Raja” in Mamala village, Leihitu sub-district, Central Maluku district, Maluku province, in June-August 2022. The descriptors used referred to Tropical Fruit Descriptors, with some modifications. The clove “Raja” that were characterized belonged to the farmers and consisted of 30 accessions of cloves that were over twenty years old. The characterization variables included the characters of trees, stems, branches, leaves, flowers, fruits, and seeds. The results of Hierarchical Cluster Analysis (HCA) on 30 plant samples based on 54 morphological characters obtained two accession groups with a dissimilarity coefficient of 41%. The results of the Principle Component Analysis (PCA) got a total diversity of 70.5% where the first group consisted of accessions of cloves “Raja” group I having identifiable characters in the form of leaf area, leaf length, leaf width, and leaf tip shape; while the second group of clove accessions of “Raja” group I in the form of stem circumference, petiole length, flower length, fruit length, fruit width, and fruit weight. Characteristics of accession of “Raja” cloves group II had distinctive morphological traits in the form of crown shape, upper surface of leaves, lower surface of leaves, leaf thickness, leaf texture, old leaf color, shoot color, leaf tip color, leaf aroma, leaf spiciness, flower stalk length, and seed color.